Airborne observations of regional variation in fluorescent aerosol across the United States. Issue 3 (3rd February 2015) - Perring, A. E.; Schwarz, J. P.; Baumgardner, D.; Hernandez, M. T.; Spracklen, D. V.; Heald, C. L.; Gao, R. S.; Kok, G.; McMeeking, G. R.; McQuaid, J. B.; Fahey, D. W.
Abstract Airborne observations of fluorescent aerosol were made aboard an airship during CloudLab, a series of flights that took place in September and October of 2013 and covered a wideband of longitude across the continental U.S. between Florida and California and between 28 and 37 N latitudes. Sampling occurred from near the surface to 1000 m above the ground. A Wideband Integrated Bioaerosol Sensor (WIBS‐4) measured average concentrations of supermicron fluorescent particles aloft (1 µm to 10 µm), revealing number concentrations ranging from 2.1 ± 0.8 to 8.7 ± 2.2 × 104 particles m−3 and representing up to 24% of total supermicron particle number. We observed distinct variations in size distributions and fluorescent characteristics in different regions, and attribute these to geographically diverse bioaerosol. Fluorescent aerosol detected in the east is largely consistent with mold spores observed in a laboratory setting, while a shift to larger sizes associated with different fluorescent patterns is observed in the west. Fluorescent bioaerosol loadings in the desert west were as high as those near the Gulf of Mexico, suggesting that bioaerosol is a substantial component of supermicron aerosol both in humid and arid environments. The observations are compared to model fungal and bacterial loading predictions, and good agreement in both particle size and concentrations is observed in the east. In the west, the model underestimated observed concentrations by a factor between 2 and 4 and the prescribed particle sizes are smaller than the observed fluorescent aerosol. A classification scheme for use with WIBS data is also presented.